New Technologies in the Service of Seniors - Zapędowska-Kling, Kaja Anna (Acta Universitatis Lodziensis. Folia Oeconomica, 2016)
This article emphasizes the importance of development of new interdisciplinary branch of science called gerontechnology. The main goal of this publication is to reflect on the opportunity to adapt new technologies in the service of elderly people. In the first part I review the potential fields of application of new technologies in different spheres of life of an old person. I focus mostly on technologies used in social care, healthcare, those stimulating social and civic participation, as well as those aiming at education and entertainment. In the second part I point at various barriers and limitations that impede the applicability of new technologies on the practical ground. In the third part I elaborate on moral and ethical dilemmas which are inextricably associated with the emergence of new technologies and their exploitation by humans. Conclusions include, among others, a postulate to incorporate telecare and telemedicine solutions into the mainstream senior policy in Poland.